Ancient libraries and Renaissance humanism : the De bibliothecis of Justus Lipsius - Hendrickson, Thomas (Brill's studies in intellectual history, 2017)
"The De bibliothecis of Justus Lipsius was the first monograph on library history. It followed a long series of minor treatments in the works of the humanists, from Petrarch to Fulvio Orsini. The De bibliothecis proved to be a seminal achievement, both in redefining the scope of library history and in articulating a vision of a public, secular, research institution for the humanities. It was repeatedly reprinted and translated, plagiarized and epitomized. Through the end of the nineteenth century, scholars turned to it as the ultimate foundation for any discussion of library history. In Ancient Libraries and Renaissance Humanism, Hendrickson presents a critical edition of Lipsius's work with introductory studies, a Latin text, English translation, and a substantial historical commentary"--Provided by publisher